LAPAROSCOPIC TREATMENT OF COMPLICATIONS OF PANCREATIC NECROSIS - A. G. Bukhvalov; V. N. Bordunovskiy (Креативная хирургия и онкология, 2017)
The paper analyzes the results of treatment of 38 patients with complicated forms of  pancreatic necrosis from 2000 to 2010. The treatment has do neby newly proposed method  dynamic  medical  bursopancrealaparoscopy  with  ultrasonic  cavitation  in  an  antiseptic solution using the original multi-drainage implant nickelide titanium shape  memory.Patients  who  underwent  conventional  treatment  relaparotomy,  marked  the  highest rate of postoperative complications (94,3%). number of remedial relaparotomy on average  7,  mortality  78.6%.  Minimally  invasive  technique  has  reduced  complications  to  18,2%, mortality up to 12,4%, the number of relaparotomy 1-2, the economic costs decreased by 5,8 times.